Analisis Keuntungan Pedagang Ternak Babi Di Pasar Hewan Bolu Kecamatan Tallunglipu Kabupaten Toraja Utara - Kartoni, Desri Kartoni; Sheyoputri, Aylee Christine Alamsyah; Azuz, Faidah (PALLANGGA: Journal of Agriculture Science and Research, 2024)
Pigs are animals that are widely farmed and traded at the Bolu Animal Market, and are suitable for businesses in the Toraja community. This research was carried out with the aim of finding out the profits of pig traders at the Bolu Animal Market, Tallunglipu District, North Toraja Regency. This research was carried out at the Bolu Animal Market, Tallunglipu District, North Toraja Regency from April to May 2023. This sample was determined using a saturated sample. Respondents totaled 33 people. The research data consists of primary and secondary data. The results of the research show that the average total cost of pig traders at the North Bolu Animal Market is IDR 161,792,918/month and the average income of traders is IDR 189,839,394/month, as well as the average trader profit is IDR 28,046,476/month. Babi adalah hewan yang banyak diternakkan dan diperdagangkan di Pasar Hewan Bolu, dan cocok bagi usaha masyarakat Toraja tersebut. Penelitian ini dilaksanakan dengan tujuan untuk mengetahui besar keuntungan pedagang ternak babi di Pasar Hewan Bolu Kecamatan Tallunglipu Kabupaten Toraja Utara. Penelitian ini dilaksanakan di Pasar Hewan Bolu, Kecamatan Tallunglipu, Kabupaten Toraja Utara pada bulan April sampai bulan Mei 2023. Penentuan sampel dilakukan secara sampel jenuh. Responden berjumlah 33 orang. Data penelitian terdiri dari data primer dan sekunder. Hasil penelitian menunjukkan bahwa rata-rata total biaya pedagang ternak babi di Pasar Hewan Bolu Utara sebesar Rp.161.792.918/bulan dan rata-rata penerimaan pedagang sebesar Rp.189.839.394/bulan, serta rata-rata keuntungan pedagang sebesar Rp.28.046.476/bulan.